Surface nanomechanical properties of bio-modified reclaimed asphalt binder. Issue 6 (3rd June 2021) - Cavalli, M. C.; Mazza, E.; Zaumanis, M.; Poulikakos, L. D.
Abstract : In this work, three different bio-based rejuvenators were added to the reclaimed asphalt pavement (RAP) binder: a vegetable oil, a cashew nut shell oil and a tall oil. To better understand the microstructural morphology, atomic force microscopy (AFM) was used before and after aging. Quantitative nanomechanical mapping (QNM) showed how the addition of rejuvenators affected the surface elastic moduli of RAP. Changes of the microstructure in modified RAP binders as a function of aging treatments were seen. Generally, the microstructures show four domains topographically, while two distinct domains are present in the phase image. It has been observed that these two different domains correspond to zones with different mechanical properties. Comparison between the "bees" surface's elastic moduli and the bulk elastic moduli for a virgin bitumen showed that surface's moduli were consistently higher than the bulk moduli contributing to the formation of the "bee" structures. "Bees" were observed to be composed of periodic ripples with a wavelength in the order of 400 nm for the aged virgin binder and 600 nm for the unaged one while amplitude equal to 8 and 15 nm for the aged and unaged case respectively. The results presented in this paper contribute to an improved understanding of the link between surface and bulk properties of bitumen.